3D printing of carbon fiber composite : the future of composite industry? - Yeong, Wai Yee (2021)
Fabricating composite parts with high fiber loading and design flexibility has always been a challenge. In the recent issue of Matter, Shi and co-workers showed that high fiber loading can be achieved using localized in-plane thermal assisted (LITA) 3D printing. Coupled with robotic arm, it provides a promising way to fabricate lightweight and high-performance continuous fiber reinforced thermoset composites with great design flexibility. Is 3D Printing of carbon fiber composite the inevitable revolution for the composite industry? We discuss the challenges and potentials briefly here toward the future of composite manufacturing.